2009
DOI: 10.1016/j.str.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Replication across Template T/U by Human DNA Polymerase-ι

Abstract: Summary Human DNA polymerase-ι (Polι) incorporates correct nucleotides opposite template purines with a much higher efficiency and fidelity than opposite template pyrimidines. In fact, the fidelity opposite template T is so poor that Polι inserts an incorrect dGTP approximately 10 times better than it inserts the correct dATP. We determine here how a template T/U is accommodated in the Polι active site and why a G is incorporated more efficiently than an A. We show that in the absence of incoming dATP or dGTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…The lack of any involvement of Pol in CPD bypass is in keeping with the biochemical studies indicating that this Pol is strongly inhibited in synthesizing DNA opposite a cis-syn TT dimer (18,19). Also, structural studies have indicated that the two covalently linked pyrimidine residues of a CPD could not be accommodated in the Pol active site (20)(21)(22). And moreover, even opposite undamaged T and C residues, Pol inserts nucleotides with a very low efficiency and fidelity (18,19).…”
Section: Pol Has No Role In Tls Oppositesupporting
confidence: 63%
“…The lack of any involvement of Pol in CPD bypass is in keeping with the biochemical studies indicating that this Pol is strongly inhibited in synthesizing DNA opposite a cis-syn TT dimer (18,19). Also, structural studies have indicated that the two covalently linked pyrimidine residues of a CPD could not be accommodated in the Pol active site (20)(21)(22). And moreover, even opposite undamaged T and C residues, Pol inserts nucleotides with a very low efficiency and fidelity (18,19).…”
Section: Pol Has No Role In Tls Oppositesupporting
confidence: 63%
“…The binding site S 1 is composed of residues located in the fingers subdomain (see Figure 3a or 4a). However, in contrast to the replicative Pol where the binding site S 1 has a high affinity for the unpaired bases and/or the sugar-phosphate backbone of the ssDNA template, the binding site S 1 in the Y-family Pol has a very low or even no affinity, which is consistent with the available structural studies [27,28,32,41,42]. The binding site S 2 , which is composed of residues located in the thumb domain and mainly in the LF domain (see Figure 3a or 4a), has a high affinity for dsDNA, which is also consistent with the available structural studies [27,28,32,41,42].…”
Section: Methodssupporting
confidence: 85%
“…The structure of pol ι in a ternary complex with a template dT and incoming dATP was modeled on the BrU/dGTP (PDB code 3H4D) published structures (34). The BrU is replaced by a normal thymine, and the dGTP is replaced by dATP.…”
Section: Methodsmentioning
confidence: 99%